Proposing a Scientific Taxonomy Production Lecturer: application of the methodology in a federal institution of higher education (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4102.187-209In Brazil and the around the world, the pressure for research and papers in higher education institutions has grown tremendously in the last years. This usually to be an issue in the called research universities, but now it is spreading to other educational institutions including those which purpose to graduate professionals for military career. In this context, this paper aims to present a study on the performance of professors of a Federal Higher Education Institution dedicated to training young people for military career in Brazil. To do so, we conducted a multivariate statistical cluster analysis to create taxonomy to classify and assess the professors according to a set of indicators of scientific publications and activities. The main source of data was the “Lattes Platform” that comprises curricula vitae of most of Brazilian researchers. The results allowed us to classify the professors into three distinct groups: "teacher-oriented professors", "professors in transition" and "research-oriented professors".